Potential of cogon grass (imperata cylindrica) as an alternative fibre in paper-based industry - Mohd Kassim, Angzzas Sari; Mohd Aripin, Ashuvila; Ishak, Nadiah; Hairom, Nur Hanis Hayati; Fauzi, Noor Akhmazillah; Razali, Nor Faizah; Zainulabidin, Muhd Hafeez (Asian Research Publishing Network (ARPN), 2016)
Non-wood plants were examined as alternative fibre due to the limited origin resources in paper production. In Malaysia, Imperata cylindrica was used as renewable materials to obtain cellulosic pulps to produce paper and hence preventing the environmental problems. The chemical compositions, fibre dimension, pulp and mechanical properties of I. cylindrica were investigated for application in paper-based production. The surface morphology of hand sheet was also visualized. The chemical compositions involved in this study (holocellulose, cellulose, lignin, ash, hot water and 1% NaOH solubilities) were determined according to the chlorite method, Kurscher-Hoffner approach and TAPPI test method. Meanwhile, fibre dimension were measured following the Franklin method. The mechanical properties of the hand sheet (tensile, burst and tear indices) were measured according to the TAPPI test method. Scanning Electron Microscopy (SEM) was used to visualize the surface morphology of I. cylindrica hand sheet. The I. cylindrica has lower amount of lignin (5.67%), hot water (3.83%) and 1% sodium hydroxide solubilities (19.6%) than polished C.tataria, switch grass and Palmyra palm fruit. Although I. cylindrica contains high felting rate (139), the sheets produced showed higher tensile index (45.06 Nm/g), burst index (3.90 kPam2 /g) and tear index (2.17 mNm2 /g) compared to other published non-wood fibers. From SEM images, sheets of I. cylindrica contained abundant, straight and smooth fibre. In conclusion of the characteristic study, I. cylindrica is a good potential alternative fibre in the paper-based industry.